Evaluating Profitability of Red Mud Based Geopolymer Brick by Using The Cost Benefit Analysis Framework - Kevin Heinrich Pesch; Raden Aswin Rahadi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Red mud is a byproduct of Bayer process in alumina refinery which become a major problem in the industry. The waste causes alumina refinery to spend significant amount of capital and operational expenditure to handle and was historically have caused environmental damage to its surrounding environment. To fill the research gap, this work is design to define the cost and benefit of producing geopolymer brick based of red mud by using the Cost Benefit Analysis framework. The cost is determined by the capital and operational expenditure of constructing a geopolymer brick factory and benefit was determine by the amount of cashflow the factory would generate. The work is done in PT CBJ, a new alumina refinery based at Mempawah, West Kalimantan, Indonesia which in the future will produces approximately 30 million tons of red mud. The research showed the proposed project will potentially generating a positive present value cashflow worth $126,159,703.58 from processing an annual 1.5 million ton of red mud and $901,318.85 from 6,892 ton of red mud annual processing. However, the BCR only shows 1.02 and 1.03 ratio from both scenarios. Additionally, the sensitivity analysis shows some variables are way too sensitive after price changes which conclude the project is risky to execute.